2011
DOI: 10.1002/hyp.7651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uncertainties in meteorological forcing data and land surface parameters on global estimates of terrestrial water balance components

Abstract: Abstract:The quality of near-surface meteorology and land surface parameters strongly influences the simulation of terrestrial water balance components by land surface models. In this article, the sensitivity of global estimates of terrestrial water balance components to uncertainties in meteorological forcing data and land surface parameters is investigated using the SWAP land surface model and different global datasets. The latter were prepared within the framework of the International Satellite LandSurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
0
37
0
1
Order By: Relevance
“…Most of this work has used relatively simple lumped and semidistributed hydrological models that represent watersheds with area ranging between 100 and 10,000 km 2 (Sorooshian and Dracup, 1980;Gupta et al, 1998;Andréassian et al, 2001;Vrugt et al, 2003;Muleta and Nicklow, 2005;Balin et al, 2010;McMillan et al, 2010;Vaze et al, 2010, amongst many others Troy et al (2008), Gosling and Arnell (2011), Nasonova et al (2011) and Pappenberger et al (2011). Not only do GHMs pose significant computational challenges, they also require a wealth of input data to accurately characterize global scale variations in land-use, soil type, elevation, climate conditions, and groundwater table depths (amongst others).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of this work has used relatively simple lumped and semidistributed hydrological models that represent watersheds with area ranging between 100 and 10,000 km 2 (Sorooshian and Dracup, 1980;Gupta et al, 1998;Andréassian et al, 2001;Vrugt et al, 2003;Muleta and Nicklow, 2005;Balin et al, 2010;McMillan et al, 2010;Vaze et al, 2010, amongst many others Troy et al (2008), Gosling and Arnell (2011), Nasonova et al (2011) and Pappenberger et al (2011). Not only do GHMs pose significant computational challenges, they also require a wealth of input data to accurately characterize global scale variations in land-use, soil type, elevation, climate conditions, and groundwater table depths (amongst others).…”
Section: Introductionmentioning
confidence: 99%
“…The second study, published in Gosling and Arnell (2011) used an ensemble of 9 different scenarios from 21 different GCMs to analyze the impact of forcing data uncertainty. More recently, Nasonova et al (2011) investigated the effect of different forcing datasets on the SWAT simulated water balance. Results demonstrate that the simulated surface runoff strongly depends on the precipitation dataset being used.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the very strong dependence of computed continental water flows on applied climate input (Biemans et al 2009;Döll and Fiedler 2008;Guo et al 2006;Müller Schmied et al 2014;Nasonova et al 2011). Not only precipitation, but also radiation data are strong drivers of water flows and storages around the globe, while temperature data have the strongest impact in case of snow and ice.…”
Section: Uncertain Climate Inputmentioning
confidence: 99%
“…However, to obtain reliable hydrological simulations from LSMs, several uncertainties need to be tackled. Their main sources are: model physics 20 (Dirmeyer, 2011;Beck et al, 2016); land surface parameters (Douville, 1998;Milly and Shmakin 2002); and atmospheric forcing (Ngo-Duc et al, 2005;Decharme and Douville, 2006;Nasonova et al, 2011). The experiments of Guo et al (2006b) found that atmospheric forcing uncertainties affect LSM hydrological simulations as much as uncertainties stemming from the models themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we use long time series of remote sensing retrievals: GIMMS LAI data are available from 1981 to 2011; and ESA-CCI SSM covers the whole simulation period. Several studies evaluated the impacts of forcing uncertainties on large-scale LSM simulations: Guo et al (2006) tested the sensitivity of soil moisture 20 simulations forced by several meteorological forcing datasets; Decharme and Douville (2006) and Szczypta et al (2012) looked at the impact of forcing precipitation errors on river discharge simulations; Materia et al (2010) analysed the sensitivity of simulated river discharge to changes in the atmospheric forcing data; Nasonova et al (2011) investigated the impacts of forcing and surface parameter uncertainties on simulated runoff and evapotranspiration; Liu et al (2016) ran multi-forcing and multi-model experiments to compare simulated and observed evapotranspiration. To our best knowledge, 25 the extensiveness of the presented assessment exceeds those of previous studies focused on assessing LSM sensitivity to atmospheric forcing uncertainty.…”
Section: Introductionmentioning
confidence: 99%